SISTEM INFORMASI PENJUALAN DI RUMAH MAKAN BU WENI - , DODI AQUARI T ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Sales Information System At Rumah Makan Bu Weni was needed to assist and simplify the process of record of food sales and reports preparation. The sales still done by manually and the reports was made by a lot of paper , which is caused the reservation record and report preparations can not run fungsionally, effective, efficience and on time Sales Information System At Rumah Makan Bu Weni was built by using Visual Studio 2012 and MySQL database. This system information is used for processing data, such as admin data, material data, product data, customer data, warehouse data, supplier data, stock data, cashier data, purchase data, cooked data, sales data and report data. Sales Information System At Rumah Makan Bu Weni is a system that can be used to provide output in making reports of stock data, purchase report, production report, and sales report. The report data can be presented in daily, monthly, yearly and can be viewed as tables.